2010
DOI: 10.1080/19440041003636646
|View full text |Cite
|
Sign up to set email alerts
|

Survey of lead, cadmium, mercury and arsenic in seafood purchased in Campania, Italy

Abstract: Lead, cadmium, mercury and arsenic were surveyed in fresh catch, farmed and frozen marine fish, cephalopods and mussels marketed in Campania (Italy), and the population's weekly intake from seafood was assessed. A total of 162 specimens of fish and cephalopods and 30 pools of mussels were analyzed. Pb levels in fresh catch species ranged between <20 and 689 ng/g; in farmed from <20 to 438 ng/g and in frozen from <20 to 541 ng/g. Cd values ranged in fresh catch seafood from <0.8 to 19.8 ng/g; in farmed from <0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 7 publications
6
11
1
1
Order By: Relevance
“…This value accounted approximately for 20% of the recent TWI established by EFSA. Cd EWIs comparable with that found in this study have been previously reported by other authors (Martorell et al 2001;Llobet et al 2003;Rubio et al 2006;Cirillo et al 2010). An higher estimated weekly intake (approximately 40% of the standard TWI) was noticed by Mun˜oz et al (2005) for fish and shellfish.…”
Section: Estimates Of CD Pb and Hg Intakesupporting
confidence: 93%
See 2 more Smart Citations
“…This value accounted approximately for 20% of the recent TWI established by EFSA. Cd EWIs comparable with that found in this study have been previously reported by other authors (Martorell et al 2001;Llobet et al 2003;Rubio et al 2006;Cirillo et al 2010). An higher estimated weekly intake (approximately 40% of the standard TWI) was noticed by Mun˜oz et al (2005) for fish and shellfish.…”
Section: Estimates Of CD Pb and Hg Intakesupporting
confidence: 93%
“…Previous literature revealed a comparable range of EWIs with respect to that found in this study for the total population and median consumers in Italy. In detail, Cirillo et al (2010) noticed lower results with respect to that found in this study for Italian median consumers (approximately 30% of the standard PTWI for methyl-Hg). A lower percentage with respect to the standard PTWI, that is, 10% for fish and shellfish, was also found by Mun˜oz et al (2005) for a population in Santiago, Chile.…”
Section: Estimates Of CD Pb and Hg Intakecontrasting
confidence: 81%
See 1 more Smart Citation
“…1C). The concen-trations of arsenic are not presented since all samples displayed values lower than the attained limit of detection (Table 2S) which is in accordance with literature data that indicate very low As amounts for the only characterized species, L. vulgaris (Cirillo et al, 2010).…”
Section: Elements In Edible Tissues Of Squidssupporting
confidence: 75%
“…Nutritionists recommend regular fish intake (Cirillo et al, 2010). Fish consumption is beneficial for health because of its proteins, polyunsaturated essential fatty acids (eicosapentaenoic acid, docosahexaenoic acid), minerals (calcium, iron, selenium, zinc, etc.)…”
Section: Introductionmentioning
confidence: 99%